[Stykkishólmur Harbor] - Streng, Evelyn Fiedler (1975)
Photograph of Stykkishólmur Harbor. A stone dock lined with black circular structures sits in the blue water surrounded by white boats. A white house with a red roof sits to the left of a rectangular house on a grassy patch of land overlooking the water to the right. Two, grey, rectangular, stone buildings sit along the water on the right edge of the photograph. A line of cars are parked on the harbor in the bottom of the photograph.